Problems in the theoretical foundation of the functional-equivalent approach - G. J. C. Jordaan (Acta Theologica)
The functional-equivalent approach to Bible translation is based on a specific view of communication, viz. that it is a process which takes place within a closed cultural circle. This view of  communication results in a view of the Bible as a time-bound (and not a time-directed) document which can communicate only in the closed circle of sender-message-first readers within their own socio-historical environment. Consequently it is seen as the task of the translator to make the Bible communicate to modern man via a process of transformation of the Biblical message. This  transformation is conducted in a manner which corresponds with the idea that textual form and message can be separated. For Christians who view the Bible as God’s Word which is time-directed but not time-bound, and at the same time God’s Word which communicates with believers of all time, these theoretical viewpoints of the functional-equivalent approach are problematic.